Doege-Potter Syndrome: A case report: Síndrome de Doege – Potter: Un reporte de caso - Segura Nuñez, Patricia (2024)
Doege-Potter syndrome is a rare paraneoplastic syndrome characterized by a benign or malignant mesenchymal tumor associated with persistent hypoglycemia. We present the case of a 70-year-old woman with a 4-year illness characterized by productive cough, oppressive pain in the left hemithorax, and progressively increasing dyspnea. The chest tomography revealed an extensive solid tumor in the lower 2/3 of the left hemithorax. An ultrasound-guided transthoracic biopsy of the tumor was performed. The histopathological study reports a solitary fibrous tumor and immunohistochemistry: STAT6 positive. Therefore, she underwent a thoracotomy with excision of the tumor. After surgery, glucose values normalized. The patient met the criteria for Doege-Potter syndrome, a rare entity.